Power and Leadership in Wawacan Abdul Muluk: Islamic Values in Classical Sundanese Manuscripts - Muhammad Al Hafidz; Rian Ananda Putra; Dedi Supriadi; Asep Achmad Hidayat; Yan Nurcahya; Abdul Aziz (UIN Sunan Gunung Djati Bandung, 2026)
This study examines the representation of power and leadership in the Wawacan Abdul Muluk, a classic Sundanese literary work that holds significant value in Indonesian literary heritage. Through textual analysis and literary hermeneutics, this study aims to identify the leadership values ​​contained in the manuscript, particularly those related to the concept of power from an Islamic perspective. The results show that Wawacan Abdul Muluk presents an ideal leadership model, emphasising three main dimensions: the legitimacy of power derived from noble descent and moral virtue; the exercise of power oriented towards justice and the welfare of the people; and the regeneration of leadership through education and character building. This manuscript reflects the integration of Islamic values ​​with the Sundanese leadership tradition, emphasizing the importance of morality, competence, and social responsibility in exercising power. The findings of this study contribute to understanding the concept of leadership in classical Indonesian literature and its relevance to the development of leadership grounded in local and Islamic values in the contemporary era.